Halitosis: a review of basic principles - Naila Aparecida de Godoi Machado; Paulinne Junqueira Silva Andresen Strini; Mario Olavo Pena Carneiro; Roberto Bernardino Júnior; Alfredo Júlio Fernandes Neto (Universidade Estadual de Campinas, 2016)
Halitosis, also known as bad breath or oral malodor, is the general term used to describe any disagreeable odor in expired air, regardless of whether the odorous substances originate from oral or non-oral sources. Bad breath can be detrimental to one's self-image and confidence, causing social, emotional and psychological anxiety. This paper provides a comprehensive review of the historical background, prevalence, social aspects and pathological causes of halitosis as well as the dental professional's responsibility.